Molecular spectrum of secretome regulates the relative hepatogenic potential of mesenchymal stem cells from bone marrow and dental tissue. Issue 1 (December 2017) - Kumar, Ajay; Kumar, Vinod; Rattan, Vidya; Jha, Vivekananda; Pal, Arnab; Bhattacharyya, Shalmoli
Abstract Liver regeneration is a spontaneous process that occurs after liver injury, but acute liver failure is a complex and fatal disease which is difficult to treat. Cell-based therapies are promising alternative therapeutic approach for liver failure and different cell sources have been tested in this regard. We investigated the comparative hepatogenic potential of human bone marrow stem cells (BMSC) with stem cells derived from human dental pulp (DPSC), apical papilla (SCAP) and follicle (DFSC) during this study. Hepatogenic potential of stem cells was assessed by functional assays at both genetic and protein level. We observed higher expression of most of the hepatic markers post differentiation in DPSCs compared to other cell types. LC-MS/MS analysis of stem cell secretome revealed the presence of different proteins related to hepatogenic lineage like growth arrest specific protein 6, oncostatin M, hepatocyte growth factor receptor etc. Interactome and Reactome pathway analysis revealed the interaction of DPSC/SCAP secretome proteins and these proteins were found to be associated with various pathways involved in lipid transport and metabolism. To the best of our knowledge, this is the first study regarding detailed investigation of hepatogenic potential of BMSCs v/s DMSCs (DPSC, SCAP & DFSC) along-with secretome characterization.